Patients' perspective on the chronic pain classification in the 11th revision of the International Classification of Diseases (ICD-11): results from an international web-based survey - Korwisi, Beatrice; Hay, Ginea; Forget, Patrice; Ryan, Deirdre; Treede, Rolf-Detlef; Rief, Winfried; Barke, Antonia (Pain, 2024)
The 11th revision of the International Classification of Diseases and Related Health Problems (ICD-11) aims at improving the lives of persons with the lived experience of chronic pain by providing clearly defined and clinically useful diagnoses that can reduce stigma, facilitate communication, and improve access to pain management, among others. The aim of this study was to assess the perspective of people with chronic pain on these diagnoses. An international web-based survey was distributed among persons with the lived experience of chronic pain. After having seen an information video, participants rated the diagnoses on 8 endorsement scales (eg, diagnostic fit, stigma) that ranged from −5 to +5 with 0 representing the neutral point of no expected change. Overall ratings and differences between participants with chronic primary pain (CPP) and chronic secondary pain (CSP) were analyzed. N = 690 participants were included in the data analysis. The ratings on all endorsement scales were significantly higher than the neutral point of 0. The highest ratings were obtained for “openness” (2.95 ± 1.93) and “overall opinion” (1.87 ± 1.98). Participants with CPP and CSP did not differ in their ratings; however, those with CSP indicated an improved diagnostic fit of the new diagnoses, whereas participants with CPP rated the diagnostic fit of the new diagnoses similar to the fit of their current diagnoses. These results show that persons with the lived experience of chronic pain accept and endorse the new diagnoses. This endorsement is an important indicator of the diagnoses' clinical utility and can contribute to implementation and advocacy.
Gesehen am 20.11.2024